HUBUNGAN TINGKAT KEBISINGAN DENGAN TEKANAN DARAH PADA PEKERJA GROUND HANDLING DI BANDAR UDARA INTERNASIONAL ADISUTJIPTO YOGYAKARTA - Catarina Citra Puspa Dewi; Onny Setiani; Mursid Rahardjo (Fakultas Kesehatan Masyarakat Universitas Diponegoro, 2018)
Adisuptjipto International Airport Yogyakarta has busy fligth services which causing noises. Noise exposure which exceed the threshold limit can cause a phisiological changes to blood pressure. This research had a purpose to determine the correlation of noise exposure with blood pressure on ground handling workers in Adisutjipto International Airport Yogyakarta. This research used observational analytic research with cross sectional approach. Ground handling workers of Adisutjipto International Airport Yogyakarta were used as subject in this research. Result of noise exposure in Apron A > 85dBA, noise exposure in Apron B ≤ 85 dBA. Paired sample T-test result has mean value of systolic blood pressure increase is 10,561 mmHg with significant value 0.000 (significant level < 0.05), where as mean value of diastolic blood pressure increase is 5.561 mmHg with significant value 0.000 (significant level <0.05). Chi-square test result between noise exposure with systolic blood pressure are (p=0,014; OR= 5,625) and diastolic blood pressure are (p= 0.028; OR= 4.156). the conclusion of this research present there is a significant difference (systolic blood pressure, diastolic blood pressure) between before and after working (affected to noise exposure). There is correlation between noise exposure with blood pressure on ground handling workers in Adisutjipto International Airport Yogyakarta. Advice to ground handling workers to always use hearing protection device.